Pengembangan Bandicam Berbasis Power Point Sebagai Media Pembelajaran Seni Rupa PGSD - Ridha Sarwono (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
This study aims to develop a Power point-based Bandicam learning media in the fine arts subject for Elementary School Teacher Education at Darul Ulum University Islamic Center Sudirman. This study adapts the development model according to (Borg, W, R. & Gall, 1983) as well as (Sukmadinata, 2007) which includes three stages, namely (1) the preliminary study stage, (2) the product draft preparation stage and (3) the development stage. and evaluation In assessing validity involves two validators, namely material expert validator, media expert validator, and one language validator. The subjects of this study involved 10 elementary school teacher education students at the Darul Ulum Islamic Center Sudirman University as a practical test. For data collection using a questionnaire. The results of this study indicate that the media that the author has developed is stated to be very valid and very practical to use in fine arts courses. With an average validation of 90% with a very valid category, and an average practical of 86.75 with a very practical category.